Alley Cropping System to Increase Corn Crop Production and Agricultural Productivity in Dry Land - Amirudin, Amirudin; Muhibuddin, Andi; Musa, Yunus; Kadekoh, Indrianto; Mas’ud, Hidayati (Journal of Tropical Crop Science, 2025)
Alley cropping is an agroforestry system that plants annual crops or food crops between alleys formed by hedges of trees or shrubs. This study aims to determine the effects of the alley cropping system, the provision of Gamal (Gliricidia sepium) biomass, and the doses of N, P, and K fertilizers on corn production. The study was conducted in 2022 at the educational plantation area, Integrated Farming System, Faculty of Agriculture, Bosowa University, Bontoramba Village, Pallangga Subdistrict, Gowa Regency, South Sulawesi, Indonesia. The experimental design used was a split plot with and without hedgerow plant treatment as the main plot and doses of N, P, and K as subplots. The subplots consist of the control or without fertilizers,  P fertilizer only at 100 kg.ha-1 SP-36, K fertilizer only at 100 kg.ha-1 KCl, N  and K (250 kg.ha-1 Urea, 100 kg.ha-1 KCl), N and P (250 kg.ha-1 Urea, 100 kg.ha-1 SP-36), and N, P and K (250 kg.ha-1 Urea, 100 kg.ha-1 SP-36, 100 kg.ha-1 KCl). The research showed that the alley-cropping system increased corn production from 4,690 to 6,089 tons.ha-1, with an average increase of 50% compared to corn production without the alley-cropping system. The N, P, and K fertilization produced the best average corn yields. The alley-cropping system achieved the highest land productivity compared to those without the alley-cropping system.